2007
DOI: 10.1007/bf03177394
|View full text |Cite
|
Sign up to set email alerts
|

The role of shape memory alloy on impact response of glass/epoxy laminates under low temperature

Abstract: The paper aims to evaluate the impact response of glass/epoxy laminates with embedded shape memory alloy (SMA) subject to low velocity impact at various temperatures. For the goal, the impact tests were performed by using an instrumented impact-testing machine at three temperatures: 293K, 263K and 233K for the baseline (laminates without SMA wires) and SMA laminates (laminates with embedded SMA wires). And the resultant damages were inspected through the scanning acoustic microscope (SAM). Also, based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ibekwe et al [8] have experimentally studied the impact and residual load carrying capacity of unidirectional and cross-ply laminates at low temperatures. Kang et al [9] have experimentally studied the damage behaviour of glass/epoxy laminates with embedded SMA wire subjected to low-velocity impact under low temperature. Metin Sayer et al [10] have studied and reported the impact behaviour of hybrid composites (carbon-glass fibre/epoxy), subjected to both low-velocity impact and various temperatures ranging from −20 to 60 • C. The effect of temperature on maximum energy, maximum deflection, maximum impact force, ductility and compression after impact was studied at different low impact energy levels (8, 15 and 25 J) with the temperature range of 50-120 • C. The effect of temperature in the range of 50-120 • C on impact response at different energy levels such as impact force, energy has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ibekwe et al [8] have experimentally studied the impact and residual load carrying capacity of unidirectional and cross-ply laminates at low temperatures. Kang et al [9] have experimentally studied the damage behaviour of glass/epoxy laminates with embedded SMA wire subjected to low-velocity impact under low temperature. Metin Sayer et al [10] have studied and reported the impact behaviour of hybrid composites (carbon-glass fibre/epoxy), subjected to both low-velocity impact and various temperatures ranging from −20 to 60 • C. The effect of temperature on maximum energy, maximum deflection, maximum impact force, ductility and compression after impact was studied at different low impact energy levels (8, 15 and 25 J) with the temperature range of 50-120 • C. The effect of temperature in the range of 50-120 • C on impact response at different energy levels such as impact force, energy has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Composite structures in general are susceptible to a wide range of damage and defects, which can occur during manufacture as well as during service [2][3][4] [6][7][8]. Also, although it is expected that protective materials on vessels can enhance their resistance to low velocity impact, the impact resistance is greatly affected by constituent materials, geometry and their lay-ups, and even the shape of the indenter [9,10]. Therefore, more research is necessary to understand the impact damage behavior of composite vessels with protective materials applied to the surface.…”
Section: Introductionmentioning
confidence: 99%